A Topology Based Address Selection Technique for Network Virtualization Environment - Soni K.; Upadhyay N.M.; Singh J.; Srivastava A. (My University, 2025)
Network Virtualization is a concept about the distribution of resources for easy access, accounting, rapid connection sharing, and release. Therefore, to make this possible, it is necessary to manage modern data centers effectively. However the resources from computer and storage have virtualized by applying service providers and infrastructure providers techniques which is quite effective, but a comprehensive solution for the network virtualization has not been developed yet. Since the selection of source address and the destination address is very difficult. So this paper will analyze the essential components of network virtualization which have point out into six processing steps of simple and unique observation. One is specifying the network-related requirements, such as source address, destination address and another one is, processing over the unconventional path in a methodical and adaptable manner. This paper introduces a topology-based address selection technique. In complex network architecture like Distributed Overlay Virtual Ethernet network, selection of the correct node is quite difficult from which any data will pass through. At last, this paper demonstrates the scalability and the efficiency of the solution. © 2020, Springer Nature Singapore Pte Ltd.